The struggle for Syria in context of the gas war - Sadiq, Salloum Feras (Journal of the Belarusian State University. International Relations, 2019)
The aim of this article is to expose the role of discovered gas and planned gas-pipelines-routes along the eastern Mediterranean in the Syrian war, which began in 2011 and has been ongoing until today. This article examines the importance of gas in the XXI century and the clash of interests between superpowers and regional countries, manifested in gas pipeline projects passing through the territory of the Syrian Arab Republic (SAR). The volume of natural resources found in Syria and the role of the gas factor in this crisis are also analyzed. It is emphasized that Damascus’s position on Western projects like gas pipelines or the Greater Middle East contributed to the intensifying of the conflict. The discovery of new gas and oil fields in the SAR and the Syrian government’s policy became one of the reasons for the intervention of several Western and regional countries to overthrow President Bashar al-Assad and thus control Syria and its wealth.
Keywords: Gas War; gas pipelines; Nabucco project; Islamic gas pipeline; South Stream; Nord Stream; Turkish Stream; Russia; United States of America; Europe; Syria; Iran; Qatar; Turkey; Saudi Arabia